Construção de equipamento para obtenção de filamentos para impressão 3D: um estudo com copolímero ABS e microcompósitos com fibras de celulose - Sanchez Junior, Miguel (2021)
This work had as main objective to assemble a set of equipment to produce polymeric filaments for 3D printing by FDM (Fused Deposition Modeling), which is compact and easy to operate in order to have control, mainly, of the diameter of the produced filament. Two types of filaments were prepared based on the acrylonitrile-co-butadiene-co-styrene (ABS) terpolymer using the equipment assembled here: a) using granules of virgin material and b) using granules of ABS / cellulose microfiber composites. Tensile, bending and impact specimens were prepared with these two types of filaments using the FDM technique and for comparative purposes, specimens with commercial ABS filament were also produced. The electromechanical equipment proved to be suitable for the manufacture of the filaments consisting of a thermal fusion unit and pellet homogenization, electromechanical pulling of the extruded filament, digital monitoring of the extruded filament diameter and electromechanical filament winding, keeping the diameter of the same constant and around 1.75 mm. The production of cellulose microfibers was carried out by acid hydrolysis of Eucalyptus grandis wood, obtaining microfibers with crystallinity greater than 83%. ABS/ cellulose fiber microcomposites were prepared by mixing in the molten state with 0.5% by weight of fiber in a co-rotating twin screw extruder. Despite the need for a refinement of the processing variables to obtain the filaments (avoiding thermal degradation), the presence of cellulose microfiber has managed to significantly improve the tensile and banding mechanical properties of ABS.